Financial Inclusion and Taxation in Digital Finance: Mediating Organizational Capabilities in Indonesian Startups - Agam Sinaga; Sunday Ade Sitorus (Universitas Mercu Buana, 2026)
Objective: This research evaluates whether financial inclusion and taxation shape the use of digital finance by Indonesian startups, both independently and through three firm-level capabilities: corporate governance, financial literacy, and technological innovation. Institutional Theory is combined with Dynamic Capability Theory to clarify how external institutional conditions are converted into organizational resources for digital financial transformation.Methodology: An explanatory quantitative survey was analyzed through Partial Least Squares Structural Equation Modeling in SmartPLS 4. From a population of 2,558 registered Indonesian startups, purposive screening produced 100 valid firm-level responses. The analysis first examined measurement reliability and validity and then assessed the direct paths and specific mediation effects in the structural model.Findings: Financial inclusion and taxation were each positively associated with digital finance through significant direct and indirect routes. Broader financial access supplies resources and connections to formal services, whereas tax requirements encourage transparent reporting, accountability, compliance, and process modernization. Governance quality, financial competence, and innovation operate jointly in translating institutional access and regulatory pressure into practical digital-finance implementation.Conclusion: Enduring digital transformation requires an enabling financial and regulatory environment together with capable internal systems. Public policy should pair inclusion and digital-tax initiatives with support for governance, financial skills, and technology readiness. Startup leaders should likewise invest in internal controls, employee competence, and digital infrastructure to strengthen competitiveness and continuity.